Exploring Iodide and Hydrogen Sulfide as ROS Scavengers to Delay Acute Rejection in MHC-Defined Vascularized Composite Allografts - Philipp Tratnig-Frankl; Alec R. Andrews; Yanis Berkane; Claire Guinier; Marion Goutard; Elise Lupon; Hyshem H. Lancia; Michael L. Morrison; Mark B. Roth; Mark A. Randolph; Curtis L. Cetrulo; Alexandre G. Lellouch (MDPI AG, 2024)
Vascularized composite allografts (VCA) face ischemic challenges due to their limited availability. Reperfusion following ischemia triggers oxidative stress and immune reactions, and scavenger molecules could mitigate ischemia-reperfusion injuries and, therefore, immune rejection. We compared two scavengers in a myocutaneous flap VCA model. In total, 18 myocutaneous flap transplants were performed in Major histocompatibility complex (MHC)-defined miniature swine. In the MATCH group (n = 9), donors and recipients had minor antigen mismatch, while the animals were fully mismatched in the MISMATCH group (n = 9). Grafts were pretreated with saline, sodium iodide (NaI), or hydrogen sulfide (H2S), stored at 4 °C for 3 h, and then transplanted. Flaps were monitored until clinical rejection without immunosuppression. In the MATCH group, flap survival did not significantly differ between the saline and hydrogen sulfide treatments (p = 0.483) but was reduced with the sodium iodide treatment (p = 0.007). In the MISMATCH group, survival was similar between the saline and hydrogen sulfide treatments (p = 0.483) but decreased with the sodium iodide treatment (p = 0.007). Rhabdomyolysis markers showed lower but non-significant levels in the experimental subgroups for both the MATCH and MISMATCH animals. This study provides insightful data for the field of antioxidant-based approaches in VCA and transplantation.